Implementasi Metode AHP dan TOPSIS dalam Penentuan Smartphone Gaming - Ika Alfiyah Noviana Ika; Zuly Budiarso (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2023)
Technological developments has a great impact on the development of types, features, specifications, and prices on smartphones that are increasingly varied. With this, people, especially game enthusiasts, have difficulty in determining smartphones according to the criteria needed. To solve this problem, we need a system that allows people to identify gaming smartphones based on certain criteria. The criteria used include RAM, battery, internal memory, processor, screen, camera, and price. This system applies the Analytical Hierarchy Process (AHP) method to obtain the weighting value of criteria and Technique for Others Preference by Similarity to Ideal Solution (TOPSIS) to produce the highest to lowest value priority ranking. From the calculation results obtained for the highest value, namely Redmi Note 9 Pro (0.787), Realme 8 (0.76), Realme 6 (0.633), Realme Narzo 50A (0.386), Realme Narzo 30A (0.379), and the lowest value Redmi Note 8 (0.127). With this system, it will make it easier for game fans to recommend the best smartphone.